Body composition - Heymsfield, Steven (Henry Stewart Talks, 2009)
Clinical applications, Historical overview, Five level model, Chronology of method development, Relationship to energy balance and outcome, Atomic level, Molecular level, Hydrodensitometry, Hydrometry, 3-compartment model, Photon Absorptiometry, Tissue-organ level, Computed tomography, Magnetic resonance imaging, Nuclear magnetic resonance, PET/fMRI, Energy expenditure, Anthropometry, Bioimpedance analysis, Summary and future directions